Plasma biomarkers of endothelial function, inflammation and oxidative stress in individuals with non‐freezing cold injury. Issue 3 (20th February 2023) - Eglin, Clare M.; Wright, Jennifer; Shepherd, Anthony I.; Massey, Heather; Hollis, Sarah; Towse, Jonathan; Young, John S.; Maley, Matthew J.; Bailey, Stephen J.; Wilkinson, Chris; Montgomery, Hugh; Tipton, Michael J.
Abstract : New Findings: What is the central question of this study? Are biomarkers of endothelial function, oxidative stress and inflammation altered by non‐freezing cold injury (NFCI)? What is the main finding and its importance? Baseline plasma [interleukin‐10] and [syndecan‐1] were elevated in individuals with NFCI and cold‐exposed control participants. Increased [endothelin‐1] following thermal challenges might explain, in part, the increased pain/discomfort experienced with NFCI. Mild to moderate chronic NFCI does not appear to be associated with either oxidative stress or a pro‐inflammatory state. Baseline [interleukin‐10] and [syndecan‐1] and post‐heating [endothelin‐1] are the most promising candidates for diagnosis of NFCI. Abstract: Plasma biomarkers of inflammation, oxidative stress, endothelial function and damage were examined in 16 individuals with chronic NFCI (NFCI) and matched control participants with (COLD, n = 17) or without (CON, n = 14) previous cold exposure. Venous blood samples were collected at baseline to assess plasma biomarkers of endothelial function (nitrate, nitrite and endothelin‐1), inflammation [interleukin‐6 (IL‐6), interleukin‐10 (IL‐10), tumour necrosis factor alpha and E‐selectin], oxidative stress [protein carbonyl, 4‐hydroxy‐2‐nonenal (4‐HNE), superoxide dismutase and nitrotyrosine) and endothelial damage [von Willebrand factor, syndecan‐1 and tissue type plasminogen activator (TTPA)]. Immediately after whole‐body heating and separately, foot cooling, blood samples were taken for measurement of plasma [nitrate], [nitrite], [endothelin‐1], [IL‐6], [4‐HNE] and [TTPA]. At baseline, [IL‐10] and [syndecan‐1] were increased in NFCI ( P < 0.001 and P = 0.015, respectively) and COLD ( P = 0.033 and P = 0.030, respectively) compared with CON participants. The [4‐HNE] was elevated in CON compared with both NFCI ( P = 0.002) and COLD ( P < 0.001). [Endothelin‐1] was elevated in NFCI compared with COLD ( P < 0.001) post‐heating. The [4‐HNE] was lower in NFCI compared with CON post‐heating ( P = 0.032) and lower than both COLD ( P = 0.02) and CON ( P = 0.015) post‐cooling. No between‐group differences were seen for the other biomarkers. Mild to moderate chronic NFCI does not appear to be associated with a pro‐inflammatory state or oxidative stress. Baseline [IL‐10] and [syndecan‐1] and post‐heating [endothelin‐1] are the most promising candidates for diagnosing NFCI, but it is likely that a combination of tests will be required.